Pengaruh Terapi Relaksasi Zikir terhadap Penurunan Tingkat Kecemasan pada Penderita Dispepsia - Citra Y Perwataningrum; Yayi Suryo Prabandari; RR Indahria Sulistyarini (JIP (Jurnal Intervensi Psikologi), 2016)
This research aimed to seek the effect of Dhikr relaxation therapy to reduce anxiety levels in dyspepsia patients. Subjects in this research were dyspepsia patients who have high and moderate levels of anxiety.Subjects in this research were eight subjects which divided into two groups; four subjects in the experimental group four subjects in the control group. The data was obtained by utilizing Hamilton Anxiety Rating Scale (HARS). This research wasa non-randomized pretest pascatest control design. Analysis to examine this hypothesis using the Mann Whitney U. The result showed that the group was given Dhikr relaxation therapy these anxiety were lower than the group wasn’t given Dhikr relaxation therapy.Keyword: Dhikr relaxation therapy, anxiety, dyspepsia